Delineating the influence of solvent fraction and temperature-dependent heat source/sink on magneto-convective flow: A response surface methodology and an artificial neural network approach - Abhilasha, S.K.; Parhi, Manoranjan; Gill, Harjot Singh; Patil, Nagaraj; Umeshaiah, M. (Archives of Thermodynamics, 2026)
The present study investigates the influence of a non-uniform heat sink/source on the unsteady flow of Boger liquid via a slowly rotating stretching disk subjected to suction and convective boundary conditions. This study is significant because it helps optimise cooling and heating processes in chemical, pharmaceutical and energy systems. The research also highlights methods for managing heat and mass transport in porous and industrial materials. Overall, it helps to improve performance, stability and energy efficiency in engineering and applied science. Dimensionless ordinary differential equations are obtained by transforming the governing partial differential equations using similarity variables. The resultant non-dimensional ordinary differential equations are solved numerically utilising the finite difference method. Furthermore, the fluid flow, mass and heat transfer are evaluated using an artificial neural network approach. Additionally, the response surface methodology is used to assess the heat transmission rate statistically. The influence of different parameters on the concentration, velocity and thermal profiles is exemplified graphically. Increasing the suction parameter, relaxation time ratio and magnetic parameter reduces the velocity profile. The thermal profile enhances as the space- and temperature-dependent heat sink/source parameters increase.